Basal Cell Ameloblastoma of Mandible: A Rare Case Report with Review - Hemant Shakya; Vikram Khare; Nilesh Pardhe; Ena Mathur; Mansi Chouhan (Case Reports in Dentistry)
Ameloblastoma is a slow-growing benign neoplasm that has a strong tendency to local invasion and that can grow to be quite large without metastasizing. Rare examples of distant metastasis of an ameloblastoma in lungs or regional lymph nodes do exist. It has an aggressive and recurrent course and is rarely metastatic. Radiographically it shares common features with other lesions such as the giant cell tumor, aneurysmal bone cyst, and renal cell carcinoma metastasis; a definitive diagnosis can only be made with histopathology. Basal cell ameloblastoma is believed to be the rarest histologic subtype in which the tumor is composed of more primitive cells and has even fewer features of peripheral palisading. Till date, only few cases of basal cell ameloblastoma have been reported in the literature. Considering the rarity of the lesion, we report here an interesting and unique case of basal cell ameloblastoma of the mandible occurring in a very old patient.